Analysis of Visitor Satisfaction With Services at The Transportation Museum - Putra, Andika; Burhanudin; Fitria, Dona (International Humanity Advance, Business & Sciences, 2025)
This research examines visitor satisfaction with services at the Museum of Transportation using a qualitative approach. The study focuses on three main aspects: staff friendliness, information clarity, and the quality of facilities. Data were collected through in-depth interviews, direct observation, and documentation, with thematic analysis employed to interpret findings. Results show that most visitors are satisfied with the staff's hospitality and attentiveness, although some noted the lack of personnel in certain areas. Regarding information clarity, visitors expressed a need for more comprehensive and accessible resources, particularly in multilingual formats. Facility quality was perceived as satisfactory, especially in terms of cleanliness, but visitors suggested improvements in accessibility and the availability of supporting amenities such as rest areas and parking. This study highlights critical areas for service improvement and provides recommendations for museum management to enhance the overall visitor experience